Hydrogen Production Methods: A Literature Review - Babaa, Saleh; Khzouz, Martin (European Journal of Applied Sciences, 2024)
Hydrogen is widely recognized as one of the keys ‘players’ in the integration process of sustainable energy systems. In this paper, the present hydrogen production techniques are presented based on their working principle, efficiency and the problems associated with them. These methods comprise Steam Methane Reforming (SMR), water electrolysis, thermochemical methods of water splitting, biologically-augurated techniques and advanced methods of water dissolving including the photoelectrochemical water splitting and the plasma reforming ones. Analysis of the past and future use of these methods.Overview